Chemical composition of oil palm (Elais guineensis) and petai kerayong (Parkia javanica) / Masfitriniza Mohd Selamin … [et al.] - Mohd Selamin, Masfitriniza; Morshidi, Syaihan; Rahmat, Ridwan; Ahmad, Mohammad Fares (2008)
This project is a study about chemical composition of Oil Palm (Elaeis guineensis) and petai kerayong (Parkia javanica). There are nine experiments have done in this study. The experiment is the determination of moisture contents, cold-water solubility, hot-water solubility, alcohol-toulene solubility, 1% NaOH solubility of wood, the percentage of lignin, holocellulose, alpha cellulose and ash in wood. The percentage of result shows the content of chemical component in wood such as extractive components, lignin, holocellulose, alpha-cellulose and ash. However, this studied must be continues for the next time to know the better results of chemical constituent of oil palm and petai kerayong.